The application of factor analysis (FA) in evaluating supplier selection criteria in PT. Wijaya Karya Beton Tbk and ranking suppliers using integration of analytical hierarchy process (AHP) and adaptive ratio assessment (ARAS) - Wahyuningsih, Tri; Ristono, Agus; Muhsin, Ahmad (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
The selection of a concrete iron supplier is critical for a long-term supply chain in the infrastructure industry. Due to the participation of various qualitative and quantitative elements, the evaluation process of concrete iron supplier selection is a difficult work for decision specialists. Because uncertainty is widespread in concrete iron supplier selection challenges, improving integrated criteria selection and supplier selection procedures has proven to be one of the most efficient and superior ways to represent practical difficulties. The current study presents a novel framework for evaluating and selecting a preferred concrete iron supplier based on Factor Analysis and the ARAS (Adaptive Ratio Assessment) method, as well as the AHP (Analytical Hierarchy Process) methodology. An enhanced technique is used in the proposed method to determine the criteria weights based on expert preferences. Next, an actual case study of the concrete iron supplier selection problem is conducted in a comprehensive setting to demonstrate the effectiveness and practicability of the suggested methodology. A sensitivity analysis is also undertaken to ensure that the stated methodology is stable. Finally, the strength of the resulting result is tested by comparing it to current methodologies. The final results show that the established framework is more consistent and powerful than other approaches already in use.